2008
DOI: 10.4012/dmj.27.221
|View full text |Cite
|
Sign up to set email alerts
|

Can CQ Be Completely Replaced by Alternative Initiators in Dental Adhesives?

Abstract: Despite good clinical acceptance, photoinitiating systems based on camphorquinone and amines raise concerns in terms of yellowing, aging, toxicity, or degradation in low pH conditions. This study aimed to prove whether CQ could be successfully replaced by alternative initiators in adhesive systems. Further, the efficiency of a prototype dual-wavelength LED (=Light Emitting Diode) curing unit was analyzed. In two commercial adhesive systems, CQ was completely replaced by Lucirin TPO. The commercial adhesives an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 13 publications
2
62
0
5
Order By: Relevance
“…However, the PPD-, TPO-, and Ir819 containing resins were polymerized with the V-LED light unit to almost the same degree of monomer conversion as that achieved with the QTH LCU, even through the V-LED light unit displays only one-fourth the power of the light radiated from the QTH LCU at the peak wavelength of 410 nm. Although other study 16) reported that experimental bonding materials containing TPO as photoinitiator were sufficiently polymerized with a dual-wavelength LED light unit with peak wavelengths at 370 and 530 nm, the peak wavelength was below 390 nm of UV light. This indicates that the V-LED light unit can achieve sufficient polymerization of resins containing visiblelight photoinitiators substituted for CQ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the PPD-, TPO-, and Ir819 containing resins were polymerized with the V-LED light unit to almost the same degree of monomer conversion as that achieved with the QTH LCU, even through the V-LED light unit displays only one-fourth the power of the light radiated from the QTH LCU at the peak wavelength of 410 nm. Although other study 16) reported that experimental bonding materials containing TPO as photoinitiator were sufficiently polymerized with a dual-wavelength LED light unit with peak wavelengths at 370 and 530 nm, the peak wavelength was below 390 nm of UV light. This indicates that the V-LED light unit can achieve sufficient polymerization of resins containing visiblelight photoinitiators substituted for CQ.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies recommended phenylpropadione as a promising alternative system for dental adhesives and resins 2,[13][14][15] . Other studies indicated that monoacyl phosphine oxide could replace CQ without diminishing the properties of resin 16) . The bisacylphosphine oxide was also introduced as a possible photoinitiator system 17) .…”
Section: Introductionmentioning
confidence: 99%
“…Las lámparas de plasma de onda baja cubren parcialmente el espectro de lucerín , PPD y canforquinona, y las lámparas de plasma de alta intensidad cubren parte del espectro de la canforquinona y PPD, pero no cubre el espectro del lucerín (3). Es importante entonces conocer el iniciador que contenga la resina para seleccionar el tipo de lámpara, y obtener un mejor resultado.…”
Section: Introductionunclassified
“…The optimal absorbance wavelengths are mostly distributed from the ultraviolet (UV) to violet visible light region; hence, photopolymerization is barely initiated by standard QTH-LCUs, and might not be initiated at all by blue LED-LCUs [4]. To overcome this problem, dual-wavelength LED-LCUs have recently been developed that combine both blue and violet LEDs [5,6].…”
Section: Introductionmentioning
confidence: 99%